Cooperative MIMO transmission scheme for clustered ad hoc networks - Wen-jiang FENG; Wei ZHAO; Dong WANG (Tongxin xuebao)
The potential of cooperative multiple-input multiple-output (CMIMO) transmission was explored.An according CMIMO transmission scheme was proposed for clustered ad hoc networks,including two critical aspects.The first was weighted cooperative node selection algorithm,which synthesized the asymmetrical bi-directional channel state information (CSI) between nodes,as well as the nodes’ residual energy and connectivity.Consequently,a set of optimal nodes was selected to develop the CMIMO system mentioned above.The second was the mechanism of establishing and maintaining virtual link between two virtual nodes.Simulation shows that the proposed CMIMO transmission scheme affords higher capacity against SISO,and the scheme with node selection is more energy-efficient than that without node selection for the 70% energy saved.